Contribution of monitoring in the academic and professional training of the monitor: experience report (Research, Society and Development, 2022)
Monitoring contributes to the personal, professional and collective growth of the monitor, as well as through experience it is possible to play relevant roles that help to associate technical-scientific knowledge. In this way, the objective is to report the contributions of monitoring in the academic and professional training of the monitor and in their preparation for future teaching. This is a descriptive study, of the experience report type, carried out from the experience of the student in the monitoring of the Mental Health Care discipline, which, in the undergraduate course in Nursing and Midwifery at UESB, is offered to students of the 6th grade. semester. This experience took place in the municipality of Jequié-Ba, from September to December 2020, corresponding to the 2020.1 semester. It is noteworthy that the monitoring provided an enriching and gratifying experience, as well as taking advantage of the approximation of pedagogical teaching activities, being the monitoring of student and teacher activities that worked as a key element for a future teaching. In addition, this moment could be used for a review and sometimes for a deepening of the topics covered and to clarify doubts that may have remained from the student's time of the discipline. It is concluded that this study understood that monitoring was a time of great performance, as the discipline could add a lot to Nursing training and to the beginning of teaching practice.